Wenn die Karriereleiter wegbricht: Fairness und der Abbau von Hierarchieebenen - Tatjana Sohr (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2005)
– This paper deals with economic motives for and personnel-management consequences of reducing the number of hierarchical levels from the point of view of fairness aspects. A transition to flat hierarchies can, under certain circumstances, have serious consequences for employees who are directly or indirectly affected; these consequences include a loss of status and/or income, reduced chances of promotion and thus diminished career prospects. In particular well-qualified employees could respond to this by moving to other firms, whilst repercussions can be expected regarding the motivation and work effort of the remaining employees. It can therefore be crucial for the success of a firm that the employees accept their treatment in the course of reorganisation measures and assess it to be fair. A written survey conducted among students is to provide first information as to the acceptance of hierarchical levels being eliminated and the associated consequences for the employees. Special emphasis is placed here on the significance of various motives for delayering and different personnel-management measures for the assessment of fairness. One key finding is that reciprocity norms have a decisive influence on the perceived fairness of a restructuring measure. In particular, disadvantages resulting from a delayering of the hierarchy are apparently more likely to be accepted if they are associated with adequate compensation from the viewpoint of the employees affected.
Keywords: 330; innerbetriebliche Hierarchie; beruflicher Aufstieg; Gerechtigkeit; Organisationsänderung - Auswirkungen; Unternehmensorganisation; Berufsverlauf; Personalwirtschaft; betrieblicher Status; Einkommenseffekte; Beförderung; Statuszuweisung; Wahrnehmung